Improving the competitiveness of agricultural input markets in Ethiopia: experiences since 1991 - Gebremedhin, Berhanu; Hoekstra, Dirk; Tegegne, Azage (IAAE, 2006)
Ethiopia, a country which was a net exporter of grains and legumes about half a century ago, is now confronted with the challenge of keeping food production at pace with its population growth, preventing declining per capita food production, and reducing its dependence on food aid. With severe land degradation and low use of soil fertility inputs, crop yields remain low. Despite demonstrated potential to boost agricultural production, sustaining productivity increase has not been achieved. This paper examines the changing roles of the market agricultural oriented development policies and strategies, for the input service delivery system at the national, regional and district level and its impact on development. This paper uses information collected through participatory rapid appraisal, community and household surveys to investigate the functioning of the input market at woreda (district) levels, and identify innovations in the input market. We find that liberalization reforms of input markets have not succeeded in improving the competitiveness of the input market and alleviating shortage of input supply, and the involvement of the private sector remains limited. Generally, the input supply situation is characterized by demand outstripping supply, especially for improved seeds. Several innovation in input supply at the woreda level have been id3entified. These include primary cooperatives and union taking responsibility of crop input supply away from the woreda Office of Agriculture and Rural development; fertilizer importation and distribution by farmer cooperatives and their union; farmer to farmer supply of seeds, seedlings and planting materials; sub-contracting the manufacture of farm equipment to small-scale private manufacturers; and the emergence of private service providers. It is recommended that the negative consequence of the involvement of the public sector in input supply on the emergence and development of the private sector deserves serious attention.